THE ROLE OF TEACHERS IN ISLAMIC EDUCATION FROM THE PERSPECTIVE OF SHAYKH MUHAMMADBIN SHALIH AL-UTSAIMIN - Ilham Rahmat; Mardianto; Zaini Dahlan (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study is motivated by contemporary educational challenges, including the dehumanization of education, moral degradation among students, secular influences, and the criminalization of teachers, which have weakened the educational role of teachers. The study aims to describe the biography of Shaykh Muhammad bin Shalih al-Uthaymin, analyze his views on the role of teachers in Islamic education, and examine their relevance to contemporary education. This research employs a qualitative approach using library research. Primary data were obtained from the works of Shaykh al-Uthaymin, while secondary data were collected from books, journals, and related scholarly sources. Data were gathered through documentation and analyzed using content analysis. The findings indicate that teachers, according to al-Uthaymin, are not merely transmitters of knowledge but also spiritual guides, moral educators, and role models. Teachers are expected to demonstrate sincerity, piety, professionalism, creativity, compassion, and responsibility for students’ intellectual, moral, and spiritual development. These concepts remain highly relevant to twenty-first-century education, particularly in strengthening character education, enhancing teacher professionalism, promoting student-centered learning, and fostering a humane and religious school culture.